Development of DNA and recombinant vaccines against toxoplasma gondii infection / Ching Xiao Teng - Ching, Xiao Teng (2016)
Toxoplasma gondii is an obligate intracellular protozoan parasite, infecting a broad range of warm-blooded hosts, including humans. T. gondii infection is a relapsing infection and causes encephalitis especially in immunocompromised patients. Miscarriage is another form of severe sequela resulting from primary T. gondii infection in pregnant women during early pregnancy. T. gondii infection occurs in livestock as well, contributing to great economic loss in the food industry. As such, it is essential to develop a vaccine to confer long-term protection from the infection. The T. gondii dense granule antigen 2 and 5 (GRA2 and GRA5) have been targeted in this study because these proteins are essential to the development of parasitophorous vacuole (PV), a specialized compartment formed within the infected host cell. PV is resistance to host cell endosomes and lysosomes thereby protecting the invaded parasite. In this study, recombinant GRA2 (rGRA2) and GRA5 (rGRA5) were produced in prokaryotic and eukaryotic expression systems and evaluated in serodiagnosis and vaccination tests. Gene fragments encoding GRA2 and GRA5 were amplified and cloned into pRSET B (prokaryotic) and pcDNA 3.1C (eukaryotic) expression vectors. Expression of recombinant GRAs-pRSET B was achieved in Escherichia coli BL21 (DE3) pLysS followed by purification through ProbondTM Purification System. Sensitivity and specificity of the purified rGRA2 and rGRA5 were assessed in western blot assays against Toxoplasma-infected human serum samples. Their sensitivity towards acute infection is 100% for rGRA2 and 46.8% for rGRA5 respectively. Almost similar sensitivity was obtained towards chronic infection (≈61%). rGRA2 and rGRA5 showed high specificity of 90% and 100% respectively when tested against Toxoplasma-negative human serum samples. Meanwhile, expression of recombinant GRAs-pcDNA 3.1C was attained in Chinese hamster ovary (CHO) cells. The recombinant vectors pcGRA2 and pcGRA5- cells produced antigenic proteins with the molecular weight in iv transfected CHO cells. Both the E. coli-expressed subunit and DNA vaccines were evaluated against lethal challenge of the virulent T. gondii RH strain in BALB/c mice. rGRA2 and rGRA5 elicited humoral and cellular-mediated immunity in the mice. High level of IgG antibody was produced with the isotype IgG2a/IgG1 ratio of ≈0.87 (p<0.001). Significant increase (p<0.05) in the level of four cytokines (IFN-γ, IL-2, IL-4 and IL-10) was obtained. The antibody and cytokine results suggest that a mix mode of Th1/Th2-immunity was elicited with predominant Th1-immune response inducing partial protection against T. gondii infection. On the other hand, the DNA vaccines pcGRA2 and pcGRA5 elicited cellular-mediated immune response with significantly higher levels of IFN-γ, IL-2, IL-4 and IL-10 (p<0.05). A mix Th1/Th2-immunity was also obtained with predominantly Th1-immune response which slightly prolonged the survival days of the immunized BALB/c mice. In conclusion, GRA2 and GRA5 have been shown to be potential candidates for diagnostic and vaccine development against T. gondii infection